Subcarpathian Ruthenia in conditions of pre-war international crisis of 1938 and territorial encroachments of neighboring states (on regional press materials) - Tetiana Kuprii; Lidiia Tymish; Leonid Panasiuk (Cхід, 2019)
Through the prism of the Subcarpathian press of the first third of the twentieth century, the tragic period of establishment of the Ukrainian statehood on the eve of World War II, the struggle for the free development of the Ukrainian nation on the territory of Subcarpathian Ruthenia due to the Munich Agreement and the dangerous political game of England, France, Germany and Italy, as well as Poland and Hungary, in the epicenter of ambitions of which Transcarpathia was caught, is delineated. Further development was given to the issues of struggle of the Ukrainians in Transcarpathia for the realization of the “peoples’ right to self-determination” in the course of the forceful formation of the joint Polish-Hungarian border after the Second Czechoslovak crisis of 1938, which had given rise to the actual division of Czechoslovakia on the one hand, and the intensification of Ukrainians’ national aspirations - on the other. The geopolitical aspects of the game of the Central Powers, as well as of Poland and Hungary in the process of “redrawing Europe”, the international peculiarities of the policy of appeasement of an aggressor of 1938 as a process of concessions and losses, in which the Transcarpathian lands remained as currency and the government of the autonomous Subcarpathian Ruthenia had to struggle alone against imperial revisionism, aggressive propaganda and destructive armed sabotage, were analyzed. Based on the Transcarpathian periodicals, the development of relations between the Carpathian Ukraine and practically the only foreign-policy partner - Germany - is shown in the context of the formation of the Hitler’s strategy of the “Eurasian Axis”, where the Ukrainian lands had a significant role. Factors of influence on the formation of the new European political reality and the role of the Ukrainian country in it are investigated. When using the press as a key source of historical data, a comprehensive picture of the Central Powers’ encroachments and aspirations and their practical intentions in an international crisis is reflected.